Corporate Governance, ESG Disclosure, and Fraudulent Financial Reporting: Evidence from the Indonesian Agricultural Products Industry - Ningtias, Putri Kharisma Ayu; Kusumaningsih, Ambar (Badan Penerbit Universitas Muria Kudus, 2026)
This study examines the relationship between corporate governance, ESG disclosure, and fraudulent financial reporting from an agency theory perspective in agricultural product companies listed on the Indonesia Stock Exchange during 2021–2024. Fraudulent financial reporting was measured using the Beneish M-Score. Corporate governance was proxied by institutional ownership and the proportion of independent commissioners, while ESG disclosure was measured using an index based on the GRI Standards 2021. This study employed a quantitative approach, with purposive sampling and Spearman correlation analysis, using IBM SPSS 26. The results showed that corporate governance and ESG disclosure were not significantly related to fraudulent financial reporting. This finding indicates that the presence of formal monitoring mechanisms and transparency of information are not necessarily effective in suppressing opportunistic management behavior. The limitations of this study include its sectoral focus and reliance on a single fraud detection model. Future research is recommended to use more substantive monitoring proxies and expand the sectors and analysis methods to gain a more comprehensive understanding.